(untitled) (Research, Society and Development, 2022)
The use of Free and Open Source Software (FOSS) not only contributes to the reduction of public spending, but also opens doors in the fields of production and circulation of knowledge, through the gain of technological independence at organizational levels. The objective of this work, therefore, was to analyze which factors influence the acceptance and use of FOSS by the servers of the Federal University of Ceará - UFC, using the Unified Theory of Acceptance and Use of Technology (UTAUT) as a research base. In this way, 349 administrative technicians and professors from the UFC in the city of Fortaleza-CE participated in a survey. The collection instrument was validated through Confirmatory Factor Analysis, which indicated the reduction of empirical data in 4 factors, with an explanation of 63% of the total variance, in addition, it presented satisfactory internal consistency in all constructs of the model, calculated through Cronbach’s alpha coefficient (>0.80). Two hypotheses proposed in the research were supported, referring to the influence of the experience with the use of FOSS on the Effort Expectation and Facilitating Conditions constructs. From the use of data mining, a total of 13,354 associations between the groups were generated, where it was evidenced that the effect of the Performance Expectation construct is stronger in young adult male workers (78 to 80%), while it is smaller in women (63%), in addition to the fact that servers more experienced in the use of these tools (71%) are more convinced that they have the resources and knowledge necessary to use them, corroborating the theoretical model.